The Cult Of Tridev In Uthamar Temple At Tiruchirappalli: A Historical Analysis - V. GIRIJA DEVI; Dr. B.PERUNDEVI (Revista Electronica de Veterinaria, 2024)
The Uttamar Temple, located in Tamil Nadu’s Trichy district, stands as a significant monument in the history of Hindu worship, particularly for its unique dedication to the Tridev-Lord Shiva, Lord Vishnu, and Lord Brahma. Unlike most temples in Tamil Nadu, where the worship of Shiva and Vishnu became predominant after the sixth century CE, the Uttamar Temple maintains the ancient tradition of revering the Tridev together. This temple, situated on the banks of the Kollidam River along the Trichy-Salem National Highway, is one of the few where the three deities are enshrined side by side. The Uttamar Temple holds a special place among the 108 Divya Desams, the sacred Vaishnava shrines revered by devotees. The temple’s architecture and iconography underscore the theological unity of Saivism and Vaishnavism, highlighting that both traditions are integral aspects of the same religious framework. Despite the rarity of temples dedicated explicitly to Lord Brahma, the Uttamar Temple includes him as a central figure in its worship, alongside Lord Shiva and Lord Vishnu. This inclusiveness reflects the temple’s broader theological significance, particularly in recognizing Brahma as part of the Tridev, thus underscoring the temple’s role in sustaining the worship of all three deities in a single sacred space.